A Shannon-Runge-Kutta-Gill Method for Convection-Diffusion Equations. (26th March 2013) - Duan, Xiaoming; Leng, Jinsong; Cattani, Carlo; Li, Caiyun
Abstract : A Shannon-Rugge-Kutta-Gill method for solving convection-diffusion equations is discussed. This approach transforms convection-diffusion equations into one-dimensional equations at collocations points, which we solve by Runge-Kutta-Gill method. A concrete example solved is used to examine the method's feasibility.